2012
DOI: 10.1016/j.postharvbio.2011.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Pheophytinase activity and gene expression of chlorophyll-degrading enzymes relating to UV-B treatment in postharvest broccoli (Brassica oleracea L. Italica Group) florets

Abstract: 1Pheophytinase (PPH) activity and gene expression of chlorophyll (Chl)-degrading 2 enzymes relating to UV-B treatment in postharvest broccoli (Brassica oleracea L. Italica 3 Group) florets were determined. PPH is involved in the dephytylation of Mg-free Chl a, 4 pheophytin (Phy) a. However, chlorophyllase (Chlase, EC.3.1.1.14) also uses Phy a as a 5 substrate to produce pheophorbide (Pheide) a by dephytylation. For an accurate 6 determination of PPH activity, the PPH protein fraction was separated from Chlase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(32 citation statements)
references
References 32 publications
0
31
0
1
Order By: Relevance
“…An acetone powder of coriander was prepared using the method described by Aiamla‐or, Nakajima, Shigyo, and Yamauchi (). One gram of frozen coriander was mixed with cold acetone (−20°C) and maintained at −20°C for 15 min, then centrifuged at 12,000 g for 5 min at 4°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An acetone powder of coriander was prepared using the method described by Aiamla‐or, Nakajima, Shigyo, and Yamauchi (). One gram of frozen coriander was mixed with cold acetone (−20°C) and maintained at −20°C for 15 min, then centrifuged at 12,000 g for 5 min at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Pheophytinase (PPH) activity was measured based on the method reported by Schelbert et al () and Aiamla‐or et al (). A total of 0.35‐ml enzyme extract was mixed with 75 ml of 2.0% (v/v) Triton‐X 100, 0.1 ml Phy a (10 mmol/L), and 0.7 ml of Tris‐HCl (pH 8.0, 50 mmol/L).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, under high salinity conditions, high concentrations of Na + may be present in the P. australis cytoplasm, which may create favorable conditions for chlorophyllase because ion concentrations can substantially influence the activities of many enzymes (Taiz and Zeiger 2010). High chlorophyllase activity favors chlorophyll degradation (Aiamla-or et al 2012). Moreover, because P. australis cannot effectively transport Na + into vacuoles of leaf cell, the water potential of guard cells is relatively constant with increasing salinity.…”
Section: Difference In Photosynthetic Tolerance To Salinity Between Pmentioning
confidence: 99%
“…However, a recent study on ripening kiwis (both 'stay-green' and yellowing varieties; Pilkington et al 2012) revealed the presence of the enzyme pheophytin pheophorbide hydrolase in increasing amounts towards fruit maturity. The enzyme catalyses the transformation of pheophytin a into pheophorbide a (Schelbert et al 2009;Aiamla-or et al 2012), suggesting pheophytin a occurring as catabolite also in fruits. Overall, the chlorophyll degradation process is complex and incompletely explored (Hörtensteiner and Kräutler 2011;Saga and Tamiaki 2012), and studies on fruits in particular are underrepresented (Barry 2009).…”
Section: Pigment Composition Varies Over Declining Total Chlorophyllmentioning
confidence: 99%